Studi Perbandingan Analisa Harga Satuan Pekerjaan Tahun 2016 Dan 2022 Bidang Cipta Karya - Kasoma, Eriku; Veronika Happy Puspasari (Jurnal Basement : Jurnal Teknik Sipil, 2023)
Cost estimation is a very important component in a construction. Estimated construction costs can be calculated using various methods, one of which is using the unit price analysis method. The unit price analysis method for work has undergone an update in 2022 which updated the method in the previous year. Therefore this research was carried out to conduct a study by directly comparing the two cost estimation methods to find out the comparison and make a record of what is the difference in the unit price analysis. the 2016 and 2022. Data analysis techniques used in this research are: literature review and direct comparison of analysis codes, job names, descriptions of resources used, resource codes, units, and coefficients. From the results of the study and direct comparison, two general criteria were obtained, namely the criteria for change and constant. In the first general criteria, there are seven more specific change criteria, namely name or code changes, changes in the description of the resources used, changes in coefficients, changes in codes and units, transfers, additions and deletions. After recording, a total of 779 comparisons were found between the 2016 and 2022 unit price analysis cost estimation methods.